Phosphorus Dynamics Associated With Organic Carbon Mineralization by Reduction of Sulfate and Iron in Sediment Exposed to Fish Farming - Mok, Jin-Sook; Choi, Ayeon; Kim, Bomina; An, Sung-Uk; Lee, Won-Chan; Kim, Hyung Chul; Kim, Jonguk; Yoon, Cheolho; Hyun, Jung-Ho (Frontiers in Marine Science, 2021)
The expansion of the aquaculture industry has resulted in accumulation of phosphorus (P)-rich organic matter via uneaten fish feed. To elucidate the impact of fish farming on P dynamics, P speciation and benthic P release along with partitioning of organic carbon (Corg) mineralization coupled to sulfate reduction (SR) and iron reduction (FeR) were investigated in the sediments from Jinju Bay, off the southern coast of Korea, in July 2013. SR in the farm sediment was 6.9-fold higher than the control sediment, and depth-integrated (0 to 10 cm) concentrations of NH4+, PO43-, and H2S in pore water of the farm sediment were 2.2-, 3.3-, and 7.4-fold higher than that in control sediment, respectively. High biogenic-P that comprised 28% of total P directly reflected the impact of P-rich fish feed, which ultimately enhanced the bioavailability (58% of total P) of P in the surface sediment of the farm site. In the farm sediment where SR dominated Corg mineralization, H2S oxidation coupled to the reduction of FeOOH stimulated release of P bound to iron oxide, which resulted in high regeneration efficiency (122%) of P in farm sediments. Enhanced P desorption from FeOOH was responsible for the increase in authigenic-P and benthic P flux. Authigenic-P comprised 33% of total P, and benthic P flux to the overlying water column accounted for approximately 800% of the P required for primary production. Consequently, excessive benthic P release resulting directly from oversupply of P-rich fish feed was a significant internal source of P for the water column, and may induce undesirable eutrophication and harmful algal blooms in shallow coastal ecosystems.